2015
DOI: 10.1080/00325481.2016.1114878
|View full text |Cite
|
Sign up to set email alerts
|

Management of gout in the real world: current practice versus guideline recommendations

Abstract: Improvements in practice by physicians would include comprehensive assessment of the patient, adoption of regular monitoring during treatment, and the provision of patient education on adherence and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…; Doghramji et al . ). Health professionals may be more likely to offer dietary advice if standardised guidelines were available; therefore, robust RCT‐level evidence is required in order to fully elucidate the effect of individual foods and dietary patterns on both SUA and gout.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Doghramji et al . ). Health professionals may be more likely to offer dietary advice if standardised guidelines were available; therefore, robust RCT‐level evidence is required in order to fully elucidate the effect of individual foods and dietary patterns on both SUA and gout.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, there is some evidence that fibre intake is protective against gout (Lyu et al 2003;Zykova et al 2015). GPs in the US and Europe have reported that they offer dietary advice to gout sufferers less often than regular uric acid testing, indicating potential missed opportunities to improve patient outcomes (Oderda et al 2014;Doghramji et al 2016). Health professionals may be more likely to offer dietary advice if standardised Aim for an ideal bodyweight * * * Avoid crash dieting * * * Avoid high-protein/low-carbohydrate diets * * Include low-fat dairy products * * Favour soya beans and vegetable sources of protein * Combine animal and vegetarian sources of protein * Favour cherries * * Restrict intake of high-purine foods (<200 mg/day total purines) * * Avoid purine-rich foods such as organ meats, shellfish and yeast extracts * * * Eat purine-rich vegetables in moderation (asparagus, beans, cauliflower, lentils, mushrooms and spinach) guidelines were available; therefore, robust RCT-level evidence is required in order to fully elucidate the effect of individual foods and dietary patterns on both SUA and gout.…”
Section: Resultsmentioning
confidence: 99%
“…5 6 Despite the availability of an increasing number and mode of actions of ULT, gout management is far from optimal. [7][8][9][10] Suboptimal treatment is related to various key barriers among both physicians and patients. [11][12][13] Importantly, a qualitative study revealed that a substantial proportion of patients receives contradictory information from different physician, contributing to poor treatment initiation and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine, non-steroidal anti-in ammatory drugs, glucocorticoids, uric acid and allopurinol, are in general use for the treatment of gout (Doghramji et al 2016). However, a lot of current medicine treating gout have various side effects, containing anaphylactic reaction, transaminase increase and gastrointestinal reaction (Engel et al 2017).…”
Section: Introductionmentioning
confidence: 99%